PENERAPAN TEKNOLOGI PRODUKSI PELET IKAN BERBASIS MAGGOT DI KAMPOENG OASE ONDEMOHEN SURABAYA SEBAGAI UPAYA PENGEMBANGAN EKONOMI SIRKULAR - Solfaine, Rondius; Haryanta, Dwi; Revitriani, Marina; Desiandura, Kurnia; Candra, Adi (Universitas Mataram, 2025)
This community service program aims to enhance the economic capacity of Kampoeng Oase Ondemohen residents through the implementation of maggot-based fish pellet production technology, as part of a circular economy development initiative. The program includes community outreach, maggot cultivation training, pellet production, organic waste management, and digital business recording. The results showed significant improvement in community knowledge and skills. Proximate analysis of the produced pellets revealed 10.21% moisture, 6.76% ash, 31.10% protein, 10.11% fat, and 41.82% carbohydrate content, indicating balanced nutrition and compliance with fish feed standards. This initiative also supports SDGs and university performance indicators